P6 A simulated emergency clinical scenario with in-situ debriefing: an effective tool in the nursing recruitment process?. (5th November 2017) - Herneman, Kathryn; McGuinness, R; Hopkins, R; Lobo, CA
Abstract : Background: Simulation is often used in high stakes assessments for doctors, but there are fewer cited examples within nursing education. This project aimed to assess the value of integrating a simulated clinical exercise into the traditional interview process for prospective Band 6 Nurses at a tertiary Intensive Care Unit (ICU). Specifically, we were interested in the correlation between the scores from the sit-down interview and the simulation, and also the role of debriefing in the assessment of the candidates' performance. Methodology: Five Band 5 ICU Nurses took part in a standard panel based interview, plus an additional clinical emergency simulation. The scenario involved a dislodged tracheostomy, and participants were expected to manage the scenario according to the National Tracheostomy Safety Project guidelines. 1 Candidates were assessed during the simulation by an observer with a set marking system, and then during their debriefing, giving them the chance to display additional knowledge. Participants' performances were filmed and qualitative feedback on their simulation and debriefing experience was collected via questionnaires. Results: Relatively good correlation existed between participants' ranking/scores for panel interview and the simulated exercise. All participants scored additional points through the structured debriefing process. Interviewers had anticipated that debriefing may help alleviate stress, but this was not evident when assessed using Russell's Circumplex Model of Affect, 2 as two participants felt more negative emotionally after the debriefing than after the scenario. All participants felt the scenario was appropriate for their level of competence, and that simulation was a valuable learning exercise and an effective tool in the interview process. Conclusions: This first attempt at integrating simulation into the interview process suggests that interviewers and participants have found it a valuable addition. In this context debriefing seems to impact on interview scores, but its effect on stress levels is unclear, and further development should include comparisons with alternative methods. We intend to further validate our simulation and debriefing scoring methods using independent review of the video footage, to see whether there is a difference between perspectives of observers who are immersed in the scenario and those who are removed from it. References: . National Tracheostomy Safety Project. Medical Resources: Interactive Algorithms . Emergency Tracheostomy Management. Retrieved May 30, 2017, from http://tracheostomy.org.uk/Templates/Interactive%20Algorithm.html . Russell JA. A circumplex model of affect. Journal of Personality and Social Psychology 1980;39:1161–1178.